AB1248 Which joints to scan by sonography to aid diagnosing early RA and remission of RA? a systematic literature review. (23rd January 2014) - Ten Cate, D.F.; Luime, J.; Swen, N.; Gerards, A.; de Jager, M.; Basoski, N.; Hazes, J.M.; Haagsma, C.; Jacobs, J.W.
Abstract : Background: Recently, new classification criteria and new remission criteria for RA have been published, requiring accurate detection of arthritis, which could be improved using ultrasonography (US) when compared to assessment by physical examination only. Although a gold standard for presence or absence of arthritis is lacking, US might be a valuable tool when identifying early RA and true remission. Objectives: To clarify whether US can improve the establishing of the diagnosis RA and the evaluation of remission, and, if so, which set of joints should be assessed by US. Methods: A systematic literature search was performed using the keywords RA, arthritis and ultrasonography in PubMed and Embase. Relevant articles were obtained and their reference lists were screened to find additional studies. One reviewer screened titles and abstracts, and extracted data; uncertainties regarding study assessment were resolved by discussion in the study group. Results: Our search yielded 1251 initial hits; 1018 papers were excluded reading the title, 199 were excluded on the basis of the abstract, and a further 41 were excluded after reading the full text of the article. There was a wide variability in the design of these studies, prohibiting pooling of the results. Five papers evaluated US in the diagnosis process of early RA, assessing 12 to 38 joints by US. 1-5 US was more sensitive than clinical examination in detecting arthritis, and US predicted progression better to persistent arthritis (OR 5.5 (95%CI: 2.6-11.9) or RA (OR 2.3 (95%CI: 1.1-4.8) than clinical examination. The data suggests that to diagnose early RA, one should at least scan bilateral MCP, wrists and MTP joints. We found 11 papers on remission, scanning sets of joints ranging in number from 6 to 44. 6-16 Often, US inflammation was detected in patients in clinical remission, irrespective of the specific set of remission criteria used. Power Doppler (PD) signs of synovitis predicted radiological progression of joint damage (OR's ranging from 1.4 (95%CI: 1.1-1.9) to 12 (95%C: 3.3-44) and flare in patients clinically in remission (OR's ranging from 6.3 (95%CI: 2.0-20) to 13 (95%CI 1.6-104)). To confirm or falsify remission, data suggests scanning at least wrist and MCP joints of the dominant hand. Conclusions: Both for the diagnosis of RA as well as the evaluation of remission, US appears to be more sensitive than clinical exam. Power Doppler ultrasound predicts radiological progression of joint damage, flare of RA patients in remission, and in patients with early RA persistence of arthritis and progression to RA better than better than grey scale ultrasound. For the diagnosis of early RA, data suggests to at least scan bilateral MCP, wrists and MTP joints, while findings from the remission studies suggest including at least wrist and MCP joints of the dominant hand. References: Filer (2011) ARD. Freeston (2010)ARD. Salaffi (2010) Clin Exp Rheumatol. Stadt (2010) ART. Wakefield (2004) ARD. Balsa (2010) Rh. Brown (2008) A&R. Brown (2006) A&R. Foltz (2011) A&R. Ozgocmen (2008) South Med J. Peluso (2011) ARD. Saleem (2009) A&R. Saleem (2011) ARD. Saleem (2010) ARD. Scire (2009) Rh. Wakefield(2007) A&R. Disclosure of Interest: None Declared